Anxiety And Depressive Disorders Toward The Main Character In Paula Hawkins’ Novel The Girl On The Train - Armyati Siregar; Dahlia D. Moelier; Asyrafunnisa Asyrafunnisa (Fakultas Sastra, Universitas Bosowa, 2022)
The purpose of the study was to categorize and explain about kinds and causes of anxiety, symptoms and causes of depressive disorder and what are the defense mechanism of main character to overcome her anxiety and depressive disorder in novel “The girl on the Train” by Paula Hawkins. The method used of this research is descriptive method with psychological approach, the writer understand the novel reading repeatedly, quoting and qualified the data who related with the research. The result of study showed that the main character had 3 kinds of anxiety and caused by environment, threat, frustration, gender, and fear. Rachel also had a symptoms of depression and caused by infertility, infidelity and divorced, loss a job and alcohol. To overcome her anxiety and depression Rachel used 3 kinds of defense mechanism such as repression, displacement, and rationalization. From explanation above it could be conclude that anxiety and depressive disorder could be happen together with the different main caused.